Material balance principle to estimate eco-efficiency of saffron-producers aiming reduction in greenhouse gas emissions in Iran - Mardani Najafabadi, M.; Rastegaripour, F.; Yavari, F.; Ahani, E. (Frontiers in Environmental Science, 2023)
During the last decades, environmental pollution has been considered one of the challenges of the agricultural sector, which has affected the relationship between the ecological and economic performance of agricultural products. In this study, the DEA-MBP approach based on the SBM model has been used to investigate the eco-efficiency of saffron farms in Iran. The main purpose of this approach is to decrease GHG emissions by mitigating the use of highly polluting production inputs. The results showed that the average eco-efficiency is estimated at 74% and is 12% lower than technical efficiency without considering environmental issues. Therefore, saffron producers are 26% far from full efficiency, and they must change their consumption of inputs and production of inputs according to environmental issues in order to achieve it. Excessive use of diesel fuel and fungicides is cause of GHG emissions in these farms. The use of sustainable and ecological cultivation methods in farms in order to reduce the consumption of chemical fertilizers and fungicides should be considered. Replacing old machinery and repairing them can also considerably reduce fuel consumption and, GHG emissions.